THE SURVEY OF DRIVING STANDARDS IN ROAD CARGO TRANSPORT (Perner's Contacts, 2019)
The paper presents survey among more than 150 Czech truck-drivers regarding the habits influencing road transport safety. Among others, the focus is on meeting driving-times regulations, tiredness, exceeding maximum allowed speeds, talking on the radio, using hands-free, and watching movies during driving. The paper describes the outcomes of the survey and analysis the influence of individual criteria on transport safety.
Keywords: road cargo transport; truck driver; road transport safety; survey